2018
DOI: 10.1155/2018/9159281
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Curcumin-Galactomannoside Complex Delivery System Improves Hepatic Function Markers in Chronic Alcoholics: A Double-Blinded, randomized, Placebo-Controlled Study

Abstract: Considering the recent interest in free (unconjugated) curcuminoids delivery, the present study investigated the efficacy of a novel food-grade free-curcuminoids delivery system (curcumin-galactomannoside complex; CGM) in improving the hepatic function markers (inflammation and oxidative stress) in chronic alcoholics. The double-blinded, placebo-controlled study randomized 48 subjects with elevated serum transaminases and gamma-glutamyl transferase (GGT) levels, who were allocated to two groups (n=24) and to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…CGM did not induce any adverse effects in the treated subjects during the study period that further support its earlier safety reports at dosages 500 –1,000 mg/day (Krishnareddy et al, 2018). Oral administration of CGM has already been proven as extremely safe and was validated to have no observable adverse effect level (NOAEL) up to 2000 mg/kg b. wt.…”
Section: Discussionsupporting
confidence: 86%
“…CGM did not induce any adverse effects in the treated subjects during the study period that further support its earlier safety reports at dosages 500 –1,000 mg/day (Krishnareddy et al, 2018). Oral administration of CGM has already been proven as extremely safe and was validated to have no observable adverse effect level (NOAEL) up to 2000 mg/kg b. wt.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the authors [42] concluded that lecithin favoured the bioavailability of demethoxycurcumin as its plasma content was found to be higher than curcumin itself, despite its low concentration in the formulation. The formulation of fenugreek fibre and 40% curcumin called CurQfen [51] yielded the highest AUC over 24 h at a dose of 1500 mg (equivalent to 600 mg curcumin). The use of soluble fibre in the formulation produced a non-digestible gel hydrocolloid that could ferment in the colon, prevent curcumin degradation in the gastrointestinal tract, and retard curcumin release resulting in a lag time of more than 5 h and less than 30% the total release after 24 h [51].…”
Section: Ingredientsmentioning
confidence: 99%
“…Once swell in the gastrointestinal tract, CGM has been shown to act as a self-emulsifying hydrogel with high mucoadhesive character, capable of delivering amphiphilic colloidal curcumin particles that can be absorbed quickly. CGM has already demonstrated its superior efficacy in a relatively low dosage [ [32] , [33] , [34] ], with improved brain bioavailability as revealed by its influence on brain waves [ 35 ], radioprotective [ 36 ] and neuroprotective effects [ 37 , 38 ]. CGM was reported to exhibit 45-fold enhancement in the bioavailability of free curcuminoids and 270-fold enhancement in the bioavailability of total curcuminoids (sum of conjugated and unconjugated), when compared to an equivalent dose of unformulated standard curcuminoids with 95 % purity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin was also found to reduce heavy metal-induced hepatotoxicity by preventing histological injury, lipid peroxidation and mitochondrial dysfunction and maintaining liver antioxidant enzyme status [ 45 ]. Supplementation of CGM at 250 mg × 2 /day has been shown to attenuate the elevated liver function enzyme markers among chronic alcoholics in 28 days [ 33 ]. Further studies on alcohol-induced cirrhotic model of rats confirmed the hepatoprotective effect of CGM through modulation of TLR4/MMP expression and hepatic cellular regeneration [ 46 ].…”
Section: Discussionmentioning
confidence: 99%